2021
DOI: 10.1021/acs.jnatprod.1c00549
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Efficacy of Secoisolariciresinol Diglucoside and Its Polymer in Rat

Abstract: Hypercholesterolemia is a risk factor for cardiovascular disease. Conventional treatment methods include lifestyle changes and pharmaceutical interventions, but recently Health Canada approved a health claim for whole ground flaxseed as an alternative treatment for hypercholesterolemia. The literature suggests flaxseed lignans are responsible for the cholesterol-reducing effects of flaxseed. In this study, 96.1% secoisolariciresinol diglucoside (SDG) and a 50% SDG enriched polymer (SDG polymer) were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…FLE supplementation to the CAFD-fed rats induced a significant reduction in body weight and ameliorated dyslipidemia as witnessed by the significant reduction in serum TC, TG, LDL, and oxLDL concomitantly with significant elevation in serum HDL when compared to the CAFD-fed rats. Such results came in alignment with previous studies utilizing FLE ( Sun et al, 2016 ; Draganescu et al, 2021 ; Sadat Masjedi et al, 2022 ) or SDG ( Pilar et al, 2017 ; Guo et al, 2021 ) . The observed increase in serum HDL-C following FLE treatment can account for the reported improvement of the endothelial function manifested in the elevated NO and GSH levels, as well as the reduced TNF-α, IL-6, and MDA levels.…”
Section: Discussionsupporting
confidence: 91%
“…FLE supplementation to the CAFD-fed rats induced a significant reduction in body weight and ameliorated dyslipidemia as witnessed by the significant reduction in serum TC, TG, LDL, and oxLDL concomitantly with significant elevation in serum HDL when compared to the CAFD-fed rats. Such results came in alignment with previous studies utilizing FLE ( Sun et al, 2016 ; Draganescu et al, 2021 ; Sadat Masjedi et al, 2022 ) or SDG ( Pilar et al, 2017 ; Guo et al, 2021 ) . The observed increase in serum HDL-C following FLE treatment can account for the reported improvement of the endothelial function manifested in the elevated NO and GSH levels, as well as the reduced TNF-α, IL-6, and MDA levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, lignans also improved insulin resistance in mice by inducing the expression of adiponectin [29], which was also an important pathophysiological process of hepatic steatosis [57,58]. A study in 2021 also showed that lignans could reduce liver steatosis score and NAFLD activity in rats [32]. ese studies further support our finding that ENL was negatively correlated with NAFLD.…”
Section: Discussionsupporting
confidence: 74%
“…Dietary isoflavone intake was negatively correlated with NAFLD in an observational study [27], and isoflavone supplementation improved insulin resistance in patients with NAFLD in a clinical trial [28]. e relationship between lignans and NAFLD has not been reported in human participants so far; only a few animal experiments have evaluated the association between lignans and hepatic steatosis, and there is no unified conclusion at present [29][30][31][32][33][34]. Furthermore, assessment of dietary phytoestrogens is difficult to cover all food sources and the metabolic transformation of phytoestrogens in the human intestine was not under consideration in the assessment, thus failing to accurately reflect real individual exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat also contains lariciresinol diglucoside. These lignan metabolites function as antioxidants and free radical scavengers, leading to decreased risk of cancer development [61,63] and hypocholesterolemic properties [64]. These compounds are predominantly concentrated in the outer layers of the grain (e.g., seed coat and pericarp), and in the aleurone layer; however, small concentrations can be found in the inner endosperm [65].…”
Section: Bioactive Phytochemicals In Wheatmentioning
confidence: 99%